Health and well-being of middle age Indonesians: An application of seemingly unrelated regression (SUR) models. Issue 3 (September 2017) - Liew, Hui-Peng
Abstract: Objective: This study used multiple indicators of health simultaneously to examine how the socio-demographic characteristics of an individual (age, gender, education, marital status, etc.) affect health and well-being in Indonesia. Methods: The empirical work of this study is based on data from the 2007 Indonesian Family Life Survey (IFLS4). This study used seemingly unrelated regression (SUR) to examine how the socio-demographic characteristics of an individual (age, gender, education, marital status, etc.) affect health and well-being in Indonesia. Results: Findings from the seemingly unrelated regression (SUR) suggest that physical, cognitive, and mental health functioning problems co-occur more commonly than expected. Conclusion: Indonesian women, those with two or more comorbid conditions, smokers, those who are divorced or separated, and those with low education should be the main targets of policy interventions designed to reduce health inequality because they experience more barriers to health and socioeconomic well-being. Highlights: Variables that measure different aspects of health should be used simultaneously to examine the sociodemographic determinants of health and well-being. Physical, cognitive, and mental health functioning problems co-occur more commonly than expected. It is crucial to understand the joint dependency of health problems.